Long-term follow-up in patients with ST-segment elevation myocardial infarction who underwent primary percutaneous coronary intervention - Klancik, Viktor; Pesl, Ladislav; Neuberg, Marek; Tousek, Petr; Kocka, Viktor (European heart journal supplements, 2022)
Long-term follow-up after primary percutaneous coronary intervention (pPCI) for ST-segment elevation myocardial infarction (STEMI) beyond 5 years is poorly described. There are no risk-stratification systems available for routine use. This retrospective, academic, two-centre analysis included consecutive patients who presented with acute STEMI between March 2008 and December 2019. In total, 5263 patients underwent pPCI; all patients were included in the analysis only once. Baseline characteristics were gathered from prospective local registries and based on initial hospitalization. The study enrolled 5263 patients who had been treated with pPCI; it found that cardiovascular mortality was the most frequent cause of death (65.0%) on long-term follow-up to 12 years. Myocardial infarction associated mortality was 27.2%. Cardiovascular mortality was dominant, including in the landmark analysis beyond 1 year. Multivariate analysis identified significant predictors for long-term cardiovascular mortality: age, history of diabetes mellitus, history of renal insufficiency, history of heart failure, Killip class, and successful pPCI at presentation. A predictive model was built to evaluate the risk of cardiovascular death with a high discrimination value (C-statistic = 0.84). Cardiovascular diseases remain the leading cause of long-term mortality after pPCI in the Central European population. Our novel predictive model provides risk stratification; it could identify patients who would experience the greatest benefit from aggressive secondary prevention measures.